Review of Specialized Degree-Granting Graduate Programs of the Department of Defense in STEM and Management - National Research Council (The National Academies Press, 2014)
The United States military is arguably the most intensely technological, complex enterprise in existence. When compared to the gross domestic products of other countries, the Department of Defense (DoD) budget ranks above all but about 20 nations. If viewed as a company, it would be the largest globally with the most employees. Major investments in weapons systems using advanced technologies provide an advantage over competing systems. Each weapon, platform, vehicle, and person in an operating force is a node in one or more advanced networks that provide the ability to rapidly form a coherent force from a large number of broadly distributed elements. DoD's ability to create and operate forces of this nature demands a competent understanding by its workforce of the composition, acquisition, and employment of its technology-enabled forces. Review of Specialized Degree-Granting Graduate Programs of the Department of Defense in STEM and Management focuses on the graduate science, technology, engineering, mathematics and management (STEM+M) education issues of the Air Force, Navy, and Marines. This report assesses the cost, benefits, and organizational placement of DoD institutions that grant degrees in STEM+M and evaluates alternative ways - for example, civilian institutions and distance learning - to ensure adequate numbers and high-quality education outcomes for DoD personnel.
Keywords: Education

Improving the Performance of America's Schools (The National Academies Press, 1995)
The purpose of this publication is to sharpen the debate on education by presenting two contrasting statements on school reform—one by Eric Hanushek, summarizing conclusions of a group of economists on the need to revise incentives to improve public school outcomes, the other by Under Secretary of Education Marshall Smith and colleagues at the U.S. Department of Education, presenting the case for standards-based school reform. Neither of these statements represents positions considered and endorsed by the STEP Board or the National Research Council.

Prospectus for National Knowledge Assessment (The National Academies Press, 1996)

Education of Architects and Engineers for Careers in Facility Design and Construction (The National Academies Press, 1995)

Developing Human Capital to Support U.S. Innovation Capacity: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Domestic and international competition for STEM talent is driving institutions across the research and innovation landscape to consider new policies and partnerships for building and managing STEM knowledge and skills. New levels of investment in human capital to increase U.S. innovation capacity and competitiveness will require coordination and collaboration among academic institutions, workforce development programs, labor organizations, companies, and funders of research and education. On October 18-19, 2022, the Government-University-Industry Research Roundtable convened a workshop for its membership and invited guests to consider the strategic priority of human capital investment in preparing the future workforce and supporting national innovation capacity. The workshop discussions examined the state of U.S. workforce preparation and considered trends in supply and demand for human capital to meet the needs of a transforming research enterprise. This publication summarizes the presentation and discussion of the workshop.
Keywords: Industry and Labor; Education

Educating Mathematical Scientists: Doctoral Study and the Postdoctoral Experience in the United States - National Research Council (The National Academies Press, 1992)
The goal of this book is to determine what makes certain doctoral/postdoctoral programs in mathematical sciences successful in producing large numbers of domestic Ph.D.s, including women and underrepresented minorities with sufficient professional experience and versatility to meet the research, teaching, and industrial needs of our technology-based society. Educating Mathematical Scientists describes the characteristics of successful doctoral/postdoctoral programs, based on the diverse set of 10 universities at which site visits were made.
Keywords: Education

Monitoring Educational Equity - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Disparities in educational attainment among population groups have characterized the United States throughout its history. Education is sometimes characterized as the "great equalizer," but to date, the country has not found ways to successfully address the adverse effects of socioeconomic circumstances, prejudice, and discrimination that suppress performance for some groups. To ensure that the pursuit of equity encompasses both the goals to which the nation aspires for its children and the mechanisms to attain those goals, a revised set of equity indicators is needed. Measures of educational equity often fail to account for the impact of the circumstances in which students live on their academic engagement, academic progress, and educational attainment. Some of the contextual factors that bear on learning include food and housing insecurity, exposure to violence, unsafe neighborhoods, adverse childhood experiences, and exposure to environmental toxins. Consequently, it is difficult to identify when intervention is necessary and how it should function. A revised set of equity indicators should highlight disparities, provide a way to explore potential causes, and point toward possible improvements. Monitoring Educational Equity proposes a system of indicators of educational equity and presents recommendations for implementation. This report also serves as a framework to help policy makers better understand and combat inequity in the United States' education system. Disparities in educational opportunities reinforce, and often amplify, disparities in outcomes throughout people's lives. Thus, it is critical to ensure that all students receive comprehensive supports that level the playing field in order to improve the well-being of underrepresented individuals and the nation.
Keywords: Education; Surveys and Statistics

Research Training in the Biomedical, Behavioral, and Clinical Research Sciences - National Research Council (The National Academies Press, 2011)
Comprehensive research and a highly-trained workforce are essential for the improvement of health and health care both nationally and internationally. During the past 40 years the National Research Services Award (NRSA) Program has played a large role in training the workforce responsible for dramatic advances in the understanding of various diseases and new insights that have led to more effective and targeted therapies. In spite of this program, the difficulty obtaining jobs after the postdoc period has discouraged many domestic students from pursuing graduate postdoc training. In the United States, more than 50 percent of the postdoc workforce is made up of individuals who obtained their Ph.D.s from other countries. Indeed, one can make a strong argument that the influx of highly trained and creative foreigners has contributed greatly to U.S. science over the past 70 years. Research Training in the Biomedical, Behavioral, and Clinical Research Sciences discusses a number of important issues, including: the job prospects for postdocs completing their training; questions about the continued supply of international postdocs in an increasingly competitive world; the need for equal, excellent training for all graduate students who receive NIH funding; and the need to increase the diversity of trainees. The book recommends improvements in minority recruiting, more rigorous and extensive training in the responsible conduct of research and ethics, increased emphasis on career development, more attention to outcomes, and the requirement for incorporating more quantitative thinking in the biomedical curriculum.
Keywords: Health and Medicine; Education

Interprofessional Education for Collaboration: Learning How to Improve Health from Interprofessional Models Across the Continuum of Education to Practice: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
Every year, the Global Forum undertakes two workshops whose topics are selected by the more than 55 members of the Forum. It was decided in this first year of the Forum's existence that the workshops should lay the foundation for future work of the Forum and the topic that could best provide this base of understanding was "interprofessional education." The first workshop took place August 29-30, 2012, and the second was on November 29-30, 2012. Both workshops focused on linkages between interprofessional education (IPE) and collaborative practice. The difference between them was that Workshop 1 set the stage for defining and understanding IPE while Workshop 2 brought in speakers from around the world to provide living histories of their experience working in and between interprofessional education and interprofessional or collaborative practice. A committee of health professional education experts planned, organized, and conducted a 2-day, interactive public workshop exploring issues related to innovations in health professions education (HPE). The committee involved educators and other innovators of curriculum development and pedagogy and will be drawn from at least four health disciplines. The workshop followed a high-level framework and established an orientation for the future work of the Global Forum on Innovations in Health Professional Education. Interprofessional Education for Collaboration: Learning How to Improve Health from Interprofessional Models Across the Continuum of Education to Practice summarizes the presentations and small group discussions that focused on innovations in five areas of HPE: 1. Curricular innovations - Concentrates on what is being taught to health professions' learners to meet evolving domestic and international needs; 2. Pedagogic innovations - Looks at how the information can be better taught to students and WHERE education can takes place; 3. Cultural elements - Addresses who is being taught by whom as a means of enhancing the effectiveness of the design, development and implementation of interprofessional HPE; 4. Human resources for health - Focuses on how capacity can be innovatively expanded to better ensure an adequate supply and mix of educated health workers based on local needs; and 5. Metrics - Addresses how one measures whether learner assessment and evaluation of educational impact and care delivery systems influence individual and population health.
Keywords: Health and Medicine; Education

The Funding of Social Knowledge Production and Application: A Survey of Federal Agencies - National Research Council (The National Academies Press, 1978)
Keywords: Education

Women: Their Underrepresentation and Career Differentials in Science and Engineering: Proceedings of a Conference - National Research Council (The National Academies Press, 1987)
Keywords: Education

The Invisible University: Postdoctoral Education in the United States. Report of a Study Conducted Under the Auspices of the National Research Council. [Richard B. Curtis, Study Director] - National Research Council (The National Academies Press, 1969)
Keywords: Education

Early Experience and Visual Information Processing in Perceptual and Reading Disorders: Proceedings of a Conference Held October 27-30, 1968, at Lake Mohonk, New York, in Association With the Committee on Brain Sciences, Division of Medical Sciences, National Research Council. Edited - National Research Council (The National Academies Press, 1970)
Keywords: Education

Approaches to the Evaluation of Sexual Harassment Prevention and Response Efforts - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Evaluation, an important component of all research, is critical to integrate into interventions addressing sexual harassment, because the targets of such harassment can suffer serious consequences, including physical and emotional harm, lost educational opportunities, and negative effects on their career. Not only are the consequences potentially severe, but the problem is pervasive across all levels of academia. Studies show that 20–50 percent of undergraduate and graduate students experience sexual harassment from faculty or staff, as well as nearly 50 percent of women faculty and staff in academia. Moreover, despite efforts in recent decades to prevent and respond effectively to sexual harassment, it remains a significant issue with no clear decline in incidence rates. This paper offers insight into selecting the appropriate methods for evaluating interventions based on evidence, case studies, and the perspectives and experiences of the authors. The goal of the paper is to provide interested parties in higher education with an introduction to methods and approaches to evaluating interventions designed to prevent and respond to sexual harassment in their institutions. This individually-authored issue paper was created by members of the Evaluation Working Group of the Action Collaborative on Preventing Sexual Harassment in Higher Education to explore the challenges and research areas related to the evaluation of a wide range of efforts to address sexual harassment, which they present in this document. The Action Collaborative on Preventing Sexual Harassment in Higher Education of the National Academies of Sciences, Engineering, and Medicine brings together academic and research institutions and key stakeholders to work toward targeted, collective action on addressing and preventing sexual harassment across all disciplines and among all people in higher education. The Action Collaborative includes four working groups (Prevention, Response, Remediation, and Evaluation) that identify topics in need of research, gather information, and publish resources for the higher education community.
Keywords: Education

Action Collaborative on Preventing Sexual Harassment in Higher Education: Year Two Annual Report of Activities - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The Action Collaborative's Year 2 Annual Report summarizes the Action Collaborative's collective progress in the 2020-2021 year, identifies areas for future focus, discusses trends in organizations' reported areas of work, and highlights work shared by member organizations and partner network organizations. A complete collection of "descriptions of work" authored by member and partner network organizations is available in the repository.
Keywords: Education

Action Collaborative on Preventing Sexual Harassment in Higher Education: Year Three Annual Report of Activities - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The Action Collaborative on Preventing Sexual Harassment in Higher Education is an initiative where over 55 colleges, universities, and other research and training organizations are identifying, researching, developing, and implementing efforts that move beyond basic legal compliance to evidence-based policies and practices for addressing and preventing all forms of sexual harassment and promoting a campus climate of civility and respect. The Partner Network of the Action Collaborative provides an additional opportunity for collective sharing across colleges and universities, research entities, higher education associations, grassroots and non-profit organizations, federal agencies, national laboratories, industry, and other stakeholder organizations. This annual report for 2021-2022 highlights the overall progress of the Action Collaborative toward its goals and summarizes the work shared by member and partner network organizations during the third year of the collaborative.
Keywords: Education

Strategies for Developing, Implementing, and Sustaining Sexual Harassment Bystander Intervention Programs for Faculty, Staff, and Graduate Students - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
To address the persistent problem of sexual harassment within higher education, research suggests that environments need to convey that sexual harassment is not a norm and actively discourage it when it does occur. One approach that researchers have identified as helping to create such environments is bystander intervention programs, which prepare and equip individuals to interrupt and intervene when harassing behavior occurs. This paper explores bystander intervention training approaches that are designed for the complex work environments within higher education, and considers how to apply the principles of bystander intervention to the experiences and environments of faculty, staff, and graduate students., Institutions within the Action Collaborative were asked a standard set of questions to learn about their experiences with commitment and buy-in from leadership, details on how the trainings were developed and what audience it was targeted to, and how the training programs were evaluated. The paper summarizes responses from seven of these institutions and ends with a call for additional research and action. This individually-authored issue paper was created by members of the Prevention Working Group of the Action Collaborative on Preventing Sexual Harassment in Higher Education to understand how institutions are addressing the gap in bystander intervention training for faculty, staff, and graduate students. The Action Collaborative on Preventing Sexual Harassment in Higher Education of the National Academies of Sciences, Engineering, and Medicine brings together academic and research institutions and key stakeholders to work toward targeted, collective action on addressing and preventing sexual harassment across all disciplines and among all people in higher education. The Action Collaborative includes four working groups (Prevention, Response, Remediation, and Evaluation) that identify topics in need of research, gather information, and publish resources for the higher education community.
Keywords: Education

Exploring Policies to Prevent "Passing the Harasser" in Higher Education - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
One troubling aspect of sexual harassment by faculty is the ability of these individuals to quietly move on to new academic positions at other institutions of higher education (IHEs) without the disclosure of their behavior. This practice is known as passing the harasser, and is exacerbated by a general lack of transparency about findings of sexual harassment in higher education. The ramifications of passing the harasser include not only failing to hold harassers accountable for their actions but also reinforcing an institutional climate in which sexual harassment is perceived as tolerated. The aim of this paper is to provide academic institutions with an examination of the landscape of practices and the considerations for implementing procedures to prevent passing the harasser, as well as examples of how some colleges and universities are addressing specific challenges, so that administrative leadership has the information they need to create policies tailored to their institution’s needs. This individually-authored issue paper was created by members of the Response Working Group of the Action Collaborative on Preventing Sexual Harassment in Higher Education to explore the challenges and potential resolutions related to policies and practices intended to prevent passing the harasser (e.g., lack of transparency in the adjudication process) as discussed in the 2018 National Academies report Sexual Harassment of Women: Climate, Culture, and Consequences in Academic Sciences, Engineering, and Medicine. The Action Collaborative on Preventing Sexual Harassment in Higher Education of the National Academies of Sciences, Engineering, and Medicine brings together academic and research institutions and key stakeholders to work toward targeted, collective action on addressing and preventing sexual harassment across all disciplines and among all people in higher education. The Action Collaborative includes four working groups (Prevention, Response, Remediation, and Evaluation) that identify topics in need of research, gather information, and publish resources for the higher education community.
Keywords: Education

Understanding and Offsetting Financial Barriers for Black Students in Science, Engineering, and Medicine: Programs, Partnerships, and Pathways: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The number of Black students in science, engineering, and medicine in the United States has remained disproportionately low over the past several decades. A number of reasons have been identified as contributing to these low numbers, including those related to finances. Financial considerations range from the most immediate - the ability of students to pay for their education and associated costs - to more structural concerns, such as inequities that created and have perpetuated a wealth gap between races and ethnic groups. On April 19-20, 2021, the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine of the National Academies of Sciences, Engineering, and Medicine organized a virtual public workshop to examine financial barriers for Black students in science, engineering, and medicine, explore existing educational programs to them, and engage stakeholders in conversations about partnerships and policies that span academia, industry, and philanthropy. This publication summarizes the presentation and discussion of the workshop.
Keywords: Education

Improving America's Schools: The Role of Incentives - National Research Council (The National Academies Press, 1996)
Reform of American education is largely motivated by concerns about our economic competitiveness and American's standard of living. Yet, few if any of the public school reform agendas incorporate economic principles or research findings. Improving America's Schools explores how education and economic research can help produce, in the words of Harvard's Dale W. Jorgenson, "a unified framework for future education reform." This book presents the perspectives of noted experts, including Eric A. Hanushek, author of Making Schools Work, on creating incentives for improved school and student performance; Under Secretary of Education Marshall S. Smith on the Clinton Administration's reform program; and Rebecca Maynard, University of Pennsylvania, on the education of the disadvantaged. This volume explores these areas: The importance of schooling to labor market success. The prospects for combining school-based management with teacher incentives to gain the best of both approaches. The potential of recent innovations in student achievement testing, including new "value-added" indicators. The economic factors involved in maintaining an adequate stock of effective teachers. The volume also explores why, despite similar standards of living, France, the Netherlands, England, Scotland, and the United States produce different levels of education achievement. Improving America's Schools informs the current debate over school reform with a fresh perspective, examples, and data. This readable volume will be of interest to policymakers, researchers, educators, and education administrators as well as economists and employers—it is also readily accessible to concerned parents and the larger community.
Keywords: Education